COMPOSITION OPERATORS ON PLURIHARMONIC HARDY SPACES ON THE UNIT BIDISC - Thi Minh Thao, Nguyen; Thu Huong, Nguyen (HNUE Journal of Science: Journal of Natural Sciences, 2026)
In this paper, we study composition operators induced by holomorphic maps Φ = (ϕ, ψ) : \(\mathbb{D}\)\(→\)\(\mathbb{D}\)2 acting from the pluriharmonic Hardy space \(H_h^2(\mathbb{D}\)2) into \(H_h^2(\mathbb{D}\)2). Using a structural decomposition of pluriharmonic functions on the bidisc into holomorphic and anti-holomorphic parts, we reduce the underlying problem to estimates on classical holomorphic Hardy spaces. These results extend the corresponding holomorphic theory to the pluriharmonic Hardy setting on the bidisc.